Dynamics of Symbolic Behavior and Paradigm Shifts in Communication in Social Media - Rohmaniyah; Alfarrah Nazrah Felisha (Kawakib: Journal of Multidisciplinary Research, 2026)
Media is an integral part of human life. The advent and development of the internet have brought new ways of communicating in social life. Social media has introduced and transformed the communication paradigm in today's society. Communication on social media is not limited by distance, time, or space. Communication can occur anywhere, anytime, without the need for face-to-face interaction. Social media can even eliminate social status, which often serves as a barrier to communication. The potential consequences of social media also require caution, as it opens up opportunities for every individual involved to freely express their opinions. However, self-control must be exercised to ensure freedom of communication that does not violate ethical boundaries and does not offend others.